2020
DOI: 10.1055/s-0040-1709700
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Thiol/Disulfide Homeostasis Parameters in the Diagnosis of Acute Appendicitis in Children

Abstract: Objective The aim of this study was to determine the role of thiol/disulfide homeostasis (TDH) parameters which are new oxidative stress markers for the diagnosis of acute appendicitis (AA) in children with abdominal pain complaints. Methods A total of 40 patients with AA and 45 patients with abdominal pain were included in this study. Two groups were compared in terms of age, gender, white blood cell count, neutrophil-to-lymphocyte ratio, C-reactive protein (CRP), appendix diameter, and TDH paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Patients with appendicitis are likely to have an elevated CRP measurement, and many studies have found that CRP is useful in diagnosing appendicitis. [1][2][3]6] Narci et al reported in their study that the CRP value was higher in the AA group [2] Duman et al stated that CRP values increased significantly in perforated appendicitis. [3] In our study, the CRP value was found to be significantly higher in the perforated appendicitis group compared to the nonperforated group.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Patients with appendicitis are likely to have an elevated CRP measurement, and many studies have found that CRP is useful in diagnosing appendicitis. [1][2][3]6] Narci et al reported in their study that the CRP value was higher in the AA group [2] Duman et al stated that CRP values increased significantly in perforated appendicitis. [3] In our study, the CRP value was found to be significantly higher in the perforated appendicitis group compared to the nonperforated group.…”
Section: Discussionmentioning
confidence: 92%
“…The most preferred laboratory tests are WBC value, NP, CRP, NLR, PLR, MPV, and serum sodium level. [2][3][4][5][6][14][15][16][17] In a meta-analysis study conducted by Acharya et al for the diagnosis of AA, the place of values such as WBC, CRP, bilirubin, procalcitonin, Ddimer and interleukin-6 in the diagnosis was investigated. Sensitivity, specificity, and AUC for WBC were 79%, 55%, and 0.75%, and 76%, 50%, and 0.80% for CRP, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement of plasma or serum thiol-disulfide balance via the colorimetric method was developed by a Turkish scientist. [21] There are many studies on OS markers and their relationship with various diseases, such as acute appendicitis, in children, [22][23][24] yet no studies exist on the relationship between acute scrotum and OS markers in children. Additionally, many studies have explored the relationship between thiol-disulfide and testis torsion; however, our study is important as the first to show thioldisulfide and IMA levels in the differential diagnosis of acute scrotum in children.…”
Section: Discussionmentioning
confidence: 99%